Determinants of Financial Literacy and its Effect on Stock Market Participation among University Students in Ghana - Blay, Marshall Wellington; Musah, Alhassan; Ayariga, Charles; Okyere, Daniel Odei (International Journal of Economics and Financial Issues, 2024)
The study examined determinants of financial literacy and stock market participation in Ghana. The study also examined the relationship between financial literacy and stock market participation among university students in Ghana. The study involved surveying 400 University of Ghana students to assess their level of financial literacy, stock market participation, and explore potential influencing factors. The study analysed data using ANOVA and multiple regression analysis. The findings of the study revealed that students exhibited limited knowledge in various financial literacy areas, including interest compounding, time value of money, inflation, money illusion, stocks, bonds, mutual funds, and investment risk diversification. Moreover, the study identified male, older, postgraduate students, and those with more working experience as comparatively more financially literate and active participants in stock market activities. Additionally, a positive relationship between financial literacy and stock market participation in Ghana was established. Other determinants of stock market participation included age, gender, course of study, and income levels. Based on these findings, it is recommended that the Ministry of Education implement significant initiatives to enhance financial literacy education among tertiary students. Furthermore, financial institutions should increase advertising efforts to promote awareness about various financial products.